Mouse bone marrow-derived mesenchymal stem cells inhibit leukemia/lymphoma cell proliferation in vitro and in a mouse model of allogeneic bone marrow transplant - SONG, NINGXIA (Int J Mol Med, 2015)
The allogeneic hematopoietic stem cell (HSC) transplantation of mesenchymal stem cells (MSCs) contributes to the reconstitution of hematopoiesis by ameliorating acute graft-versus-host disease (aGVHD). However, the role of MSCs in graft-versus-leukemia remains to be determined. In the present study, we co-cultured C57BL/6 mouse bone marrow (BM)-derived MSCs with A20 murine B lymphoma, FBL3 murine erythroleukemia and P388 murine acute lymphocytic leukemia cells. Cell proliferation, apoptosis, cell cycle progression and the amount of cytokine secretion were then measured using a Cell Counting kit-8, Annexin V/propidium iodide staining, flow cytometry and ELISA, respectively. We also established a model of allogeneic bone marrow transplantation (BMT) using BALB/c mice. Following the administration of A20 cells and MSCs, we recorded the symptoms and the survival of the mice for 4 weeks, assessed the T cell subsets present in peripheral blood, and, after the mice were sacrifice, we determined the infiltration of MSCs into the organs by histological staining. Our results revealed that the MSCs inhibited the proliferation of the mouse lymphoma and leukemia cells in vitro, leading to cell cycle arrest and reducing the secretion of interleukin (IL)-10. In our model of allogeneic BMT, the intravenous injection of MSCs into the mice injected wth A20 cells decreased the incidence of lymphoma, improved survival, increased the fraction of CD3(+)CD8(+) T cells, decreased the fraction of CD3(+)CD4(+) T cells and CD4(+)CD25(+) T cells in peripheral blood, and ameliorated the manifestation of aGVHD. The results from the present study indicate that MSCs may be safe and effective when used in allogeneic BMT for the treatment of hemotological malignancies.